Ki-67 AS A PREDICTING FACTOR OF NASOPHARYNGEAL, BREAST, AND CERVICAL CANCER: A LITERATURE REVIEW - Arifah, Arifah; Rafiq Sulistyo Nugroho; Alfred J Petrarizky (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
Background: Although the exact role remains unknown, Ki-67 is vital in cell division. Ki-67 is a nuclear nonhistone protein present in all active phases of the cell cycle. It has the potential to predict the prognosis of responsiveness to radiotherapy, chemotherapy, or endocrine therapy, estimate residual risk, and predict recurrence in many types of cancer, including nasopharyngeal cancer (NPC), breast cancer (BC), and cervical cancer (CX), and be a marker for treatment efficacy. We want to review the efficacy of Ki-67 as a predicting factor for three types of cancer, including NPC, breast, and cervical cancer, from several pieces of literature. Materials and Methods: We are conducting a literature review to describe the role of Ki-67 as a predicting factor in NPC, BC, and CX. Results: Pretreatment Ki-67 is used as an independent prognostic marker in NPC, and elevated values are associated with poor prognosis. High Ki-67 expression may indicate poorer recurrence-free survival and overall survival. A high Ki-67 index significantly correlated with adverse prognostic factors. Conclusion: A high expression of Ki-67 in NPC, breast cancer, and cervical cancer is associated with poor prognosis, poorer recurrence, and overall survival rates. Ki-67 can be considered as a valuable biomarker of many cancers. Keywords: Radiotherapy, Ki-67, nasopharyngeal cancer, breast cancer, cervical cancer